SYNTHESIS AND CHARACTERIZATION OF ENVIRONMENTALLY FRIENDLY PAPERCRETE AS A NEW MORTAR FOR BRICK PANEL INSTALLATION - Goldberd Harmuda Duva Sinaga; Mia Endang Sari Sinaga; Ruben Cornelius Siagian; Lulut Alfaris (LPPM Universitas Sangga Buana, 2023)
This research focuses on the development of lightweight and soundproof building materials using waste paper or pulp as a component, with the aim of improving quality of life and reducing environmental pollution. Papercrete, made from unused waste paper, has environmentally friendly characteristics and can be used as the main structure of buildings. The study investigated the effect of pulp on the stress behavior of panels and tested the reusability of paper as a lightweight and eco-friendly brick material. The research method involved experimental procedures, using specialized equipment and materials to determine the properties and performance of different types of concrete mixes. Results indicate that papercrete has potential as an eco-friendly construction material with physical and mechanical properties suitable for reinforcing brick panels. Further research is recommended to investigate the effect of paper chip size on concrete strength under different humidity and temperature conditions, and to analyze the environmental impact of using papercrete as a construction material. The findings suggest that papercrete holds promise as a new and sustainable construction material. Testing papercrete in real-world scenarios could provide valuable insights into its durability and suitability for different applications.